SEVEN FACTORS INFLUENCING LANGUAGE LEARNER SYSTEMS - Nirna Nirmala; Ashri Shollina; Muhammad Zen Masruri (JIPIS, 2018)
AbstractThe concept of second language acquisition and how it is described and understood has been widely debated. This paper provides an overview on the field of error analysis. It shows the interesting perspective in learner English to earlier research on second language learning. Study of the child learner’s errors emphasizes on the types of cognitive and linguistic processes that appear to be part of the language learning process. In line with the acquisition of second language, there are seven factors that may influence and characterize the language learner systems, i.e. language transfer, intralingual interference, sociolinguistic situation, modality, age, successions of approximative systems, and universal hierrchy of difficulty. Considering the approximative systems of language learners not as pathologies to be eradicated but as necessary stages in the gradual acquisition of the target system may result in a deeper understanding of language in general and a more humane approach to language teaching.Keywords: language learner system, second language acquisition AbstrakKonsep penguasaan bahasa kedua dan bagaimana mendeskripsikan dan memahaminya telah banyak diperdebatan. Artikel ini membahas tentang penguasaan bahasa kedua yang berfokus pada error analysis. Ulasan ini menunjukkan perspektif yang menarik dalam pelajar bahasa Inggris untuk penelitian sebelumnya tentang pembelajaran bahasa kedua. Studi tentang error pada anak pelajar menekankan pada jenis proses kognitif dan linguistik yang tampaknya menjadi bagian dari proses pembelajaran bahasa. Sejalan dengan akuisisi bahasa kedua, ada tujuh faktor yang dapat mempengaruhi dan mengkarakterisasi sistem pembelajar bahasa, yaitu transfer bahasa, gangguan intralingual, situasi sosiolinguistik, modalitas, usia, suksesi sistem aproksimasi, dan hierarki kesulitan yang universal. Mempertimbangkan sistem pendekatan pembelajar bahasa bukan sebagai patologi yang harus diberantas tetapi sebagai tahap yang diperlukan dalam perolehan bertahap dari sistem target dapat menghasilkan pemahaman yang lebih dalam tentang bahasa secara umum dan pendekatan yang lebih manusiawi dalam pengajaran bahasa.Kata Kunci: penguasaan bahasa, sistem pembelajar bahasa